Applications of Core Retraction in Manufacturing Low-Density Polypropylene Foams with Microcellular Injection Molding. Issue 1 (January 2018) - Kharbas, Hrishikesh; Ellingham, Thomas; Turng, Lih-Sheng
Without modifying existing part and mold designs, the conventional microcellular injection molding (MIM) process can typically save about 5–10% material without encountering problems such as incomplete filling, excessive shrinkage, or deteriorating microstructure and mechanical properties. In this study core retraction was used in combination with the MIM process to produce thick polypropylene (PP) parts (up to 7.6 mm thick) with high density reductions of 30% and 55%. The cavity volume was modified by changing the retraction distance, which enabled control of density reductions. The lowest densities were achieved with this core retraction-aided microcellular injection molding (CR-MIM) process, the results of which could not have been achieved by the conventional MIM process alone. The effects of delay time in core retraction and weight reduction on the microstructure of the core and skin layers were investigated. It was shown that the CR-MIM process yielded better microstructure and tensile properties than the conventional MIM process. Use of core retraction also yielded more consistent densities and tensile properties throughout the length of the foamed parts.